2013
DOI: 10.1002/jcla.21558
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Genotypic Detection of rpoB and katG Gene Mutations in Mycobacterium tuberculosis Clinical Isolates from Northern India as Determined by MAS‐PCR

Abstract: MAS-PCR assays can be used for rapid detection of drug-resistant TB strains in routine diagnostic practice, enabling early administration of appropriate treatment regimens to the affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
(38 reference statements)
5
17
3
Order By: Relevance
“…Eight samples had both katG and inhA promoter mutations. Various Indian studies have reported katG mutations at codon 315 in the range of 80 to 89% (22,24,32) and inhA mutations in the range of 9% to 27% in INH-resistant strains (24,25,33). In our study, the INH monoresistance rate was ϳ21% (mutation in katG, inhA, or both), which was consistent with previous reports of 11 to 22% in India (29,34).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eight samples had both katG and inhA promoter mutations. Various Indian studies have reported katG mutations at codon 315 in the range of 80 to 89% (22,24,32) and inhA mutations in the range of 9% to 27% in INH-resistant strains (24,25,33). In our study, the INH monoresistance rate was ϳ21% (mutation in katG, inhA, or both), which was consistent with previous reports of 11 to 22% in India (29,34).…”
Section: Discussionsupporting
confidence: 91%
“…2B and C). These mutations have been reported previously at frequency estimates of 47 to 81% (codon 531), 7 to 45% (codon 526), and 5.6 to 22% (codon 516) in various studies in India (20)(21)(22)(23)(24)(25) and contribute to 70 to 95% of the total rpoB gene mutations leading to RIF resistance (22,26). We found that H526N was the most frequent mutation, followed by S531L (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…In 2006 population genetics for isoniazid was studied throughout the globe, they revealed 49% mutation in katG gene in India isolates [24]. A recently Indian study, by Anamika et al found that the most common mutation in INH isolates is katG gene at codon 315 with the frequency 82.29% [25]. However, 30% of katG resistant clinical isolates of M. tb showed the frequency of KatG315 (Ser to Thr) in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…The proportion of mutation in rpoB 526 codon (30.0%) was lower than that in the study performed in India (45.22%) [29], but it was higher than the average prevalence in Asian countries in 2001 (11%) [30] and Latvia in 2012 (11.8%) [31]. The proportion of mutation in rpoB 526 codon was 14.9% in China [32].…”
Section: Discussioncontrasting
confidence: 77%
“…Moreover, mutation in codon 531 (10.0%) was lower compared to the results of other studies [33][34][35]. Yet, the proportion of mutations in codon 516 was higher than its prevalence in East Asia [30], Latvia [31], and India [29].…”
Section: Discussionmentioning
confidence: 66%